Thrombosis in three postmenopausal women receiving testosterone therapy for low libido. (July 2013) - Glueck, Charles J; Bowe, Dedrick; Valdez, Alejandro; Wang, Ping
Our hypothesis was that thrombosis occurring in postmenopausal women given testosterone (T) or testosterone–estradiol (TE) to improve libido was associated with a prothrombotic interaction between T or TE with underlying inherited procoagulants. In three previously healthy, postmenopausal, Caucasian women with no antecedent thrombosis and previously undiagnosed G20210A prothrombin gene heterozygosity, hyperhomocysteinemia and 4G4G homozygosity of the PAI-1 gene, we describe central retinal vein thrombosis and osteonecrosis that developed at 16 days, 2 months and 11 months in the three cases, respectively, after T or TE therapy was started. Exogenous T or TE in postmenopausal women may be associated with thrombosis, speculatively when it is superimposed on underlying procoagulants. This small observational case series can serve as a starting point for a larger observational study with greater detail on patient history, serum T and estradiol levels, and detailed PCR and serologic assessment of thrombophilia and hypofibrinolysis.